Pipe preparation method of aluminum-copper gradient composite material
Through the friction stir extrusion process, the shear force generated by friction heat generation and mold rotation is used to achieve low-temperature processing and one-step molding, solving the problems of complex and high cost in the existing process, and high-performance and low-cost aluminum-copper gradient composite pipes are prepared.
Patent Information
- Application Number
- CN202510302471.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-14
AI Technical Summary
The existing aluminum-copper composite pipe preparation process is complex, and it is difficult to take into account the coordinated optimization of electrical conductivity, thermal conductivity and mechanical properties. It is also high in cost and energy consumption, making it difficult to meet the needs of high-performance, low-cost and large-scale production.
The friction stir extrusion process is adopted to generate heat through the relative rotational friction between the blank and the extrusion head, combined with the shear force and axial pressure generated by the rotation of the mold, low-temperature processing and one-step molding are achieved to prepare aluminum-copper gradient composite pipes.
It significantly reduces the extrusion pressure and refines the grains, realizes the one-step molding of hollow pipes, reduces oxidation risks and equipment costs, balances conductivity and lightweight, and prepares low-cost and high-performance aluminum-copper composite materials.
Smart Images

Figure CN119794359A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a tube of an aluminum-copper gradient composite material, belongs to the technical field of metal processing, and specifically relates to a preparation and processing technology of a high-performance, lightweight composite material. Background Art
[0002] Aluminum-copper composite materials are widely used in electronic heat dissipation, new energy power systems, aerospace lightweight structures, high-end medical equipment, and chemical corrosion-resistant pipelines by combining the lightweight, low-cost, and excellent processability of aluminum with the high electrical conductivity, high thermal conductivity, and corrosion resistance of copper. For example, in the power battery system of new energy vehicles, aluminum-copper composite pipes are used in the liquid cooling circuit of battery modules, which not only reduces weight but also improves thermal conductivity. It is particularly important in high-energy density batteries and fast charging scenarios. It can effectively avoid the risk of battery thermal runaway caused by local overheating and is one of the key materials for upgrading the thermal management system of new energy vehicles. In 5G base stations, it serves as a shielding layer and heat dissipation substrate for high-frequency signal transmission, balancing signal integrity and energy consumption control. In the nuclear industry, the gradient structure takes into account both radiation protection and thermal management needs, becoming an ideal material for the pursuit of high performance and economic synergy in multiple fields.
[0003] Copper alloys have high plasticity and can be processed by traditional extrusion processes at room temperature without preheating, but traditional hot-extruded copper tubes are prone to coarse grains (size > 100μm), which affects conductivity and mechanical properties. Aluminum alloys have poor plasticity at room temperature, and hot extrusion requires heating to high temperatures (> 400°C) and applying ultra-high axial pressure (> 400MPa), resulting in high equipment costs, severe mold wear and extremely high energy consumption. High-temperature extrusion also causes rapid grain growth, with grain sizes usually > 50μm, and material strength and ductility decrease accordingly. In addition, hollow tubes require multiple processing steps such as drilling and welding, with a scrap rate of up to 15%-20%. These technical pain points have greatly limited the further application of aluminum-copper composite pipes in the fields of electronic heat dissipation, new energy power systems, aerospace lightweight structures, high-end medical equipment, and chemical corrosion-resistant pipelines.
[0004] At present, the preparation processes of aluminum-copper composite pipes mainly include extrusion molding, explosive compounding, hot pressing welding, powder metallurgy, etc., but these processes generally face many technical problems and it is difficult to take into account the coordinated optimization of electrical conductivity, thermal conductivity and mechanical properties. Due to the large difference in the melting points of aluminum and copper, extrusion molding cannot be completely metallurgically bonded during extrusion. The interface bonding of the prepared pipe is weak and needs to rely on diffusion layer or brazing reinforcement. In addition, the mold design is complex, the dual extruder heads need to be precisely synchronized, and the mold is resistant to high temperature and high pressure; the process of explosive compounding is highly complex and requires precise control of explosion parameters such as the amount of explosives, detonation point, and gap distance, otherwise it is easy to produce stratification or partial unbonding; the equipment cost of hot pressing welding is high, and high temperature and high pressure molds, high-precision temperature control systems, and vacuum or inert gas protection are required. In addition, the production efficiency is low, single-piece welding takes a long time, and it is difficult to produce continuously; the powder metallurgy preparation process is cumbersome and requires multi-step sintering and densification, which is not suitable for rapid mass production. These processes are still unable to meet the requirements of social development for high-performance, low-cost, and large-scale preparation of aluminum-copper composite materials. Therefore, it is urgent to explore new technical and process ideas to promote the efficient and green development of high-performance aluminum-copper composite materials in my country. Summary of the invention
[0005] In view of the above problems, the present invention develops a preparation method of an aluminum-copper gradient composite material suitable for high-performance requirements based on a novel stir friction extrusion process. Stir friction extrusion is an innovative solid-state technology that can directly produce metal powder or solid billet into large pipes and rods. This technology is mainly based on the conventional extrusion process, using the relative rotation friction between the billet and the extrusion head to generate heat, and realizing a new severe plastic deformation preparation process for efficient material processing and forming. During the preparation process, heat is generated between the billet and the extrusion head due to friction, and the friction heat is mainly concentrated at the mold / bill interface, and the interface metal softens. The uniaxial extrusion force applied at the same time is combined with the rotational motion of the mold, resulting in severe plastic deformation of the billet at the interface. The softened metal layer diffuses and recrystallizes under the thermal-mechanical coupling of stirring and extrusion. Its essence is a process in which a metal material continuously forms a dense and reliable ultrafine-grained material under dynamic thermal equilibrium and pressure conditions. Compared with the processing and preparation process of traditional materials, the stir friction extrusion process gives the alloy structure and performance control more degrees of freedom. Compared with the energy consumption in the process involving remelting, stir friction extrusion can save ~50% of energy due to its efficient short process. The stir friction extrusion process combines the shear force generated by the rotation of the die with the axial pressure, combined with the spiral rolling die design and low-temperature processing strategy, which significantly reduces the extrusion pressure (<50MPa), refines the grain (1-10μm) and realizes the one-step forming of hollow tubes, while reducing the oxidation risk and equipment cost, providing a breakthrough solution for the efficient and precise forming of lightweight, highly integrated aluminum-copper gradient composite materials.
[0006] The present invention realizes low-temperature processing and one-step forming to prepare aluminum-copper gradient composite pipes through the combined effect of shear force and axial pressure generated by mold rotation during the stirring friction process, which solves the technical problems of high complexity of traditional processes, high cost of large-scale production, difficulty in regulating gradient structures, insufficient interface bonding strength, etc. Through the composition gradient design, the conductivity and lightness of the composite pipe are balanced to prepare low-cost, high-performance, intelligent aluminum-copper composite materials, which has become a material preparation and processing technology supporting the global green economy and high-end manufacturing industry.
[0007] The present invention provides a method for preparing a pipe of an aluminum-copper gradient composite material, comprising the following steps:
[0008] Step 1
[0009] A blank is prepared according to the designed composition; in the blank, the copper content of at least two regions differs by more than 1wt%;
[0010] Step 2
[0011] The obtained blank is added into a silo, and an aluminum-copper gradient composite material is prepared by a friction stirring extrusion process;
[0012] When the aluminum-copper gradient composite material is prepared by the friction stir extrusion process, the initial rotation speed of the grinding head is set to 30-50 rpm / min, and the rotation speed is maintained after contacting the raw materials in the silo, so that the temperature of the grinding head gradually increases to A℃; during the preheating stage of the grinding head, the pressure applied by the hydraulic system is 0.3-0.8 MPa to ensure that the initial pressure when the grinding head contacts the raw materials is moderate to avoid premature deformation or extrusion of the material; the value of A is 180-220; when the preheating temperature of the grinding head reaches A℃, the staged heating begins.
[0013] During the first stage of heating, the grinding head speed is increased to 100~120 rpm / min, the temperature is increased to 350~400℃ (the recrystallization temperature of aluminum is about 270℃), and the hydraulic pressure is maintained at 0.5~1.0 MPa to maintain plastic fluidity; in the second stage, the speed is further increased to 150~180 rpm / min, and the temperature is increased to 450~550℃ (lower than the recrystallization temperature of copper but higher than the softening temperature of the aluminum layer). During the implementation of the second stage, the hydraulic pressure is gradually increased to 1.5~3.0 MPa to promote diffusion at the copper-aluminum interface and compensate for the low plasticity of aluminum.
[0014] Step 3
[0015] When the temperature of the grinding head rises to 450~550℃, the hydraulic pressure is adjusted according to the wall thickness of the pipe and the grinding head speed is controlled at 150~200 rpm and the mold is preheated to 300~400℃. At the same time, gradient speed control (reducing the speed at the outlet end) is used to prevent interface peeling; the specific operating steps of gradient speed control are as follows: gradient speed control specifically refers to the speed of the grinding head inlet end being 150~200 rpm, and the speed at the outlet end being reduced by 5%~15% (135~170 rpm), and the speed decreasing distribution is achieved through the axial displacement of the spiral rolling mold.
[0016] Adjust the hydraulic pressure according to the pipe wall thickness. When the wall thickness is 1-3mm, the hydraulic pressure is set to 2~4 MPa. When the wall thickness is greater than 3mm and less than or equal to 7 mm, it is set to 4~6 MPa.
[0017] Step 4
[0018] The pipe prepared by the friction stir extrusion process is cooled to 50-80°C at a cooling rate greater than 100K / s to obtain the product.
[0019] The present invention provides a method for preparing a tube of an aluminum-copper gradient composite material, wherein in step one, the density of the blank is ≥95% of the theoretical density.
[0020] In practical application, the blank may include at least three parts, which are a high copper area, a middle copper area, and a low copper area; and the middle copper area is located between the high copper area and the low copper area, the copper content of the high copper area is greater than that of the middle copper area and the low copper area, and the copper content of the middle copper area is greater than that of the low copper area.
[0021] In practical applications, the copper content of the low copper area is greater than or equal to 50%.
[0022] Preferably, the copper content of the middle copper zone is greater than or equal to 70%.
[0023] In practical applications, the high copper area, the medium copper area, and the low copper area are composed of copper and aluminum or of a copper and aluminum alloy.
[0024] When used in industry, the raw materials used to prepare the blank are A1060 aluminum alloy powder with a purity of ≥99.0% and a particle size of 20-50μm. Fine powder is used to improve the density of the blank; C1100 electrolytic copper powder with a purity of ≥99.5% and a spherical fine powder with a particle size of 20-50μm is used to improve the conductivity of the material, improve the powder fluidity, and reduce powder segregation.
[0025] The present invention discloses a method for preparing a pipe of an aluminum-copper gradient composite material, wherein the aluminum content in a high copper region is less than or equal to 10%.
[0026] The present invention discloses a method for preparing a tube of an aluminum-copper gradient composite material, wherein the aluminum content in a medium copper zone is less than or equal to 30%, but greater than the aluminum content in a high copper zone.
[0027] The present invention discloses a method for preparing a tube of an aluminum-copper gradient composite material, wherein the aluminum content in a low copper zone is less than or equal to 50%, but greater than the aluminum content in a medium copper zone.
[0028] The invention discloses a method for preparing a pipe of an aluminum-copper gradient composite material. When mixing raw material powder in a high-copper region, a three-dimensional motion powder mixer is used, and the rotation speed is controlled to be 200 rpm / min and the time is 2 hours.
[0029] The invention discloses a method for preparing a pipe of an aluminum-copper gradient composite material. When mixing raw material powder in a middle copper zone, a three-dimensional motion powder mixer is used, and the rotation speed is controlled to be 150 rpm / min and the time is 4 hours.
[0030] The invention discloses a method for preparing a pipe of an aluminum-copper gradient composite material. When mixing raw material powder in a low-copper region, a three-dimensional motion powder mixer is used, and the rotation speed is controlled to be 100 rpm / min and the time is 6 hours.
[0031] In addition to mechanical ball milling, the present invention can also use air flow mixing, wet mixing or electrostatic mixing to mix powders.
[0032] The invention discloses a method for preparing a pipe of an aluminum-copper gradient composite material. The method comprises the following steps: laying evenly mixed high-copper region raw material powder according to a set thickness, and then laying evenly mixed high-copper region raw material powder according to a set thickness; obtaining a high-copper region raw material powder layer, and then laying a medium-copper region raw material powder layer on the high-copper region raw material powder layer, and then laying a low-copper region raw material powder layer on the medium-copper region raw material powder layer; and then pressing to obtain a blank, wherein the density of the blank is ≥95% of the theoretical density.
[0033] or
[0034] The high and low copper area raw material powders are evenly mixed and laid according to a set thickness, and then the low copper area raw material powder is evenly mixed and laid according to a set thickness; a low copper area raw material powder layer is obtained, and then a medium copper area raw material powder layer is laid on the low copper area raw material powder layer, and a high copper area raw material powder layer is laid on the medium copper area raw material powder layer; and then pressed to obtain a blank, wherein the density of the blank is ≥95% of the theoretical density.
[0035] When used in industry, A1060 aluminum alloy powder with a particle size of 20-50μm and C1100 copper powder with a particle size of 20-50μm can be weighed in sections according to the high copper region (such as 90% Cu / 10% Al, 90g), the medium copper region (such as 70% Cu / 30% Al, 70g), and the low copper region (such as 50% Cu / 50% Al, 50g), and mixed by a wet mixing method: copper and aluminum powders are added to deionized water (liquid-powder ratio 1:8~1:10) respectively, and ultrasonic vibration is performed for 30 minutes to form a uniform suspension; then the high, medium and low copper region slurries are injected into the mixing cavity in turn by a peristaltic pump, and the gradient distribution of copper and aluminum powders is achieved by negative pressure suction (vacuum degree -0.05 MPa); then dried in an 80°C oven for 6 hours to obtain a gradient composite powder with a humidity of <0.5%. Subsequently, the mixed powder was loaded into a graphite mold and pressed by hot isostatic pressing (HIP) at room temperature to 450°C: in the pre-pressing stage, the pre-pressing pressure was 150 MPa for 10 minutes to initially eliminate the powder gap; in the final pressing stage, the temperature was raised to 350°C and pressurized in two stages with a gradient pressure (150→300 MPa), and the temperature was kept for 90 minutes to make the density of the blank ≥99.5% of the theoretical density.
[0036] In the present invention, the press forming is selected from at least one of cold isostatic pressing, die pressing and hot isostatic pressing.
[0037] In the present invention, the mold cold pressing process is cold-pressed by layering high copper area, medium copper area and low copper area raw material powder, and the wet mixing method can form a gradient blank with copper content decreasing along the axial direction through phased injection, flow field regulation and drying and solidification. During the pressing process, the high-density copper area maintains a stable thickness due to its low plasticity, and the low-density aluminum area is compressed first due to its high plasticity, so gradient pressurization is used in the powder pressing process. In the initial stage, a lower pressure (150 MPa) is applied to eliminate the internal pores of the blank, and then the pressure is gradually increased to the final value (300 MPa) to promote the diffusion of the copper-aluminum interface and compensate for the low plastic deformation ability of aluminum, and finally achieve the blank characteristics of continuous gradient distribution of copper and aluminum components (gradient difference ≥ 20% Cu), uniform density (≥ 95% theoretical density) and interface metallurgical bonding, which meets the requirements of zoning regulation of electrical conductivity, thermal conductivity and mechanical properties. The core is to deeply couple the spatial distribution of copper and aluminum powders with process parameters (powder addition order, flow rate, stirring intensity) to form a controllable gradient structure. The theoretical prediction can be verified by SEM / EDS and other means later.
[0038] One of the schemes for press forming is to select the following parameters: pressure of 200 MPa and holding time of 2 hours. When the cold isostatic pressing process is adopted, a rubber mold is preferred.
[0039] In the present invention, the silo material is preferably hot working die steel, and more preferably H13 steel, to ensure good wear resistance and thermal stability at high temperatures.
[0040] In industrial applications, inert gas cooling (argon flow rate 50~100 L / min) combined with a water-cooled jacket is used to achieve rapid cooling (rate ≥150 K / s). The final cooling temperature is controlled at 50~80℃ to avoid residual stress, and a nitrogen curtain is used to protect the aluminum layer from oxidation.
[0041] In addition to the friction stir extrusion process, the present invention can also use hot extrusion or cold extrusion process to form the pipe.
[0042] Beneficial Effects
[0043] The present invention provides a method for preparing a tube of an aluminum-copper gradient composite material, which has the following significant advantages compared with the prior art:
[0044] The present invention adopts a stir friction extrusion process, which utilizes the relative rotation friction between the blank and the extrusion head to generate heat, does not require high-temperature melting of metal, and reduces the energy consumption of external heat sources. Compared with hot pressing welding, energy consumption is reduced by 50%, significantly reducing production costs. The process can directly process aluminum-copper powder blanks into pipes in one step, and can achieve efficient and continuous production by adjusting the extrusion speed, which is suitable for large-scale production applications.
[0045] The composition of the aluminum-copper gradient composite material prepared by the present invention is controllable. By controlling the axial composition gradient of the mixed powder, a plurality of gradient section combinations are set: high copper area → medium copper area → low copper area. Since copper and aluminum are prone to generate interface stress due to the difference in thermal expansion coefficient, the composition design can gradually transition the copper-aluminum ratio, reduce local stress concentration, and avoid delamination or cracking. By adjusting the speed, pressure and raw material laying sequence of the stirring head, the copper-aluminum ratio can be accurately controlled along the axial distribution to avoid excessive use of high-priced copper and reduce the cost of raw materials. In addition, the friction stir extrusion process can optimize the organizational structure by regulating the processing temperature, the speed and pressure of the stirring head, refine the grains (1-10μm) and regulate the grain orientation, and balance the electrical conductivity, thermal conductivity and mechanical properties of the aluminum-copper composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 Schematic diagram of the friction stir extrusion process;
[0047] Figure 2 This is a physical picture of the aluminum-copper gradient composite pipe prepared in Example 1;
[0048] Figure 3 This is a photo of the aluminum-copper gradient composite pipe prepared in Example 2. DETAILED DESCRIPTION
[0049] Embodiment 1
[0050] A specific implementation of the present invention is as follows: first, prepare A1060 aluminum alloy powder (particle size 20-50μm) with a purity of ≥99.0% and C1100 electrolytic copper powder (particle size 20-50μm) with a purity of ≥99.5%, and divide the powder into three gradient sections according to performance requirements, namely, a high copper zone (90% Cu, 10% Al), a medium copper zone (70% Cu, 30% Al) and a low copper zone (50% Cu, 50% Al), wherein the amount of copper powder in each zone is 90g, 70g, and 50g, respectively, and the amount of aluminum powder is 10g, 30g, and 50g, respectively, and the total mass is controlled at 100g / section; then, a three-dimensional motion powder mixer is used for gradient powder mixing, and the powder is uniformly dispersed by horizontal, vertical, and rotational three-axis linkage, wherein the high copper zone is mixed at a speed of 200 rpm for 2 hours, the medium copper zone is mixed at a speed of 150 rpm for 4 hours, and the low copper zone is mixed at a speed of 100 rpm for 4 hours. The mixture was mixed at rpm for 6 hours, and the gradient distribution of copper and aluminum powders was promoted by the combination of differentiated speed and time. Subsequently, the mixed powder was loaded into a rubber mold and pressed at room temperature using a cold isostatic pressing device. The pressure was controlled at 200 MPa and the holding time was 2 hours. The density of the blank after pressing was ≥95% of the theoretical density (the blank was divided into three areas: high copper area / medium copper area / low copper area). Next, the extrusion process was carried out using a friction stirring extruder equipped with an H13 steel silo: first, the speed was set to 45 rpm during the preheating stage of the grinding head, and the speed was maintained after contacting the aluminum-copper raw materials in the silo, so that the temperature of the grinding head gradually increased to 180°C, and the hydraulic system applied a pressure of 0.5 MPa to avoid premature deformation or extrusion of the material; then it entered the temperature increase stage. During the first stage of temperature increase, the grinding head speed was increased to 100 rpm, the temperature was increased to 350°C, and the hydraulic pressure was maintained at 1 MPa to maintain plastic fluidity; in the second stage, the speed was further increased to 150 rpm, the temperature was increased to 450°C, and the hydraulic pressure was gradually increased to 1.5 MPa to promote copper-aluminum interface diffusion and compensate for the low plasticity of aluminum; in the friction extrusion stage, the hydraulic pressure needs to be adjusted according to the thickness and diameter of the pipe wall (3 MPa is set for a wall thickness of 3 mm), and the grinding head speed is controlled at 150 rpm and preheat the mold to 300℃, and prevent interface peeling by gradient speed control (i.e., the speed at the inlet end of the grinding head is 150rpm and the speed at the outlet end is 135rpm); finally, inert gas cooling (argon flow rate 50L / min) combined with a water-cooled jacket is used to achieve rapid cooling (rate ≥150 K / s), the final cooling temperature is controlled at 80℃ to avoid residual stress, and a nitrogen curtain is used to protect the aluminum layer from oxidation.
[0051] Embodiment 2
[0052] First, prepare A1060 aluminum alloy powder (particle size 20-50μm) with a purity of ≥99.0% and C1100 electrolytic copper powder (particle size 20-50μm) with a purity of ≥99.5%. According to performance requirements, the powders are divided into three gradient sections: high copper area (90% Cu, 10% Al), medium copper area (70% Cu, 30% Al) and low copper area (50% Cu, 50% Al). The amount of copper powder in each area is 90g, 70g, and 50g, respectively, and the amount of aluminum powder is 10g, 30g, and 50g respectively, and the total mass is controlled at 100g / section. Then, the airflow mixing method is used to mix the powders, and the copper and aluminum powders in the high copper area, medium copper area, and low copper area are respectively loaded into three independent silos, and the high-speed airflow generator (wind speed 15-20 m / s) is turned on, and the rotating scraper mechanism (speed 50 rpm) is used to achieve uniform mixing of copper and aluminum powders through turbulence. Subsequently, the mixed powder is loaded into a graphite mold (the inner cavity size is consistent with the target tube) (the bottom layer is high copper area powder, the middle layer is medium copper area powder, and the upper layer is low copper area powder), and the mold cold pressing method is used for pressing at room temperature: 100 MPa pressure is used in the pre-pressing stage, and the pressure is maintained for 5 minutes to preliminarily eliminate the powder gap; in the final pressing stage, the pressure is gradually increased to 300 MPa, and the pressure is maintained for 15 minutes. The density of the pressed billet is ≥90% of the theoretical density; the pressure is slowly released to demolding at normal pressure to take out the billet (the billet is divided into three areas: high copper area / medium copper area / low copper area). Then, friction stir extrusion was carried out. A friction stir extruder equipped with an H13 steel silo was used. In the preheating stage of the grinding head, the initial speed was set to 50 rpm. After contacting with the aluminum-copper mixed raw material in the silo, it maintained stable operation, so that the temperature of the grinding head gradually increased to 200°C; then it entered the heating stage. In the first stage, the speed was increased to 120 rpm, the temperature was increased to 380°C, and the hydraulic pressure was stabilized at 1.0 MPa to maintain the plastic flow of the material; in the second stage, the speed was further increased to 160 rpm, the temperature reached 480°C, and the pressure was gradually increased to 2.0 MPa to accelerate the diffusion of atoms at the copper-aluminum interface and compensate for the lack of plasticity of the aluminum matrix. In the friction extrusion stage, the pressure parameters were dynamically adjusted according to the wall thickness of the pipe: the pressure was set to 3-5 MPa when the wall thickness was 1-3 mm, and the pressure was adjusted to 5-7 MPa when the wall thickness was 5-7 mm. At the same time, the grinding head speed was controlled at 160 rpm and the mold was preheated to 300°C. The interface peeling phenomenon was effectively suppressed by gradient speed design (i.e., the speed at the inlet of the grinding head was 160rpm and the speed at the outlet was 140rpm). Finally, the argon flow rate of 70 L / min combined with the water cooling jacket was used to achieve rapid cooling (cooling rate 180K / s), and the final cooling temperature was controlled in the range of 70℃, supplemented by a nitrogen protective curtain to prevent oxidation of the aluminum layer.
[0053] Embodiment 3
[0054] Firstly, A1060 aluminum alloy powder with a particle size of 20-50μm and C1100 copper powder with a particle size of 20-50μm were weighed in sections according to the high copper region (90% Cu / 10% Al, 90g), medium copper region (70% Cu / 30% Al, 70g), and low copper region (50% Cu / 50% Al, 50g), and mixed by a wet mixing method: copper and aluminum powders were added into deionized water (liquid-powder ratio 1:8-1:10) respectively, and ultrasonically vibrated for 30 minutes to form a uniform suspension; then, the high, medium and low copper region slurries were injected into the mixing cavity in turn by a peristaltic pump, and negative pressure suction (vacuum degree -0.05 MPa) was used to achieve the gradient distribution of copper and aluminum powders (the bottom layer was the high copper region powder, the middle layer was the medium copper region powder, and the upper layer was the low copper region powder); then, they were dried in an oven at 80℃ for 6 hours to obtain a gradient composite powder with a humidity of <0.5%. Subsequently, the mixed powder was loaded into a graphite mold and pressed by hot isostatic pressing (HIP) at room temperature to 450°C: in the pre-pressing stage, a pressure of 150 MPa was used for 10 minutes to initially eliminate the powder gap; in the final pressing stage, the temperature was raised to 350°C and pressurized in two stages with a gradient pressure (150→300 MPa) for 90 minutes to make the density of the blank ≥99.5% of the theoretical density; then, the pressure of 300 MPa was maintained at 450°C for 30 minutes to promote the diffusion of copper and aluminum atoms to form a metallurgical bonding interface. Finally, the hot extrusion process was used to prepare the pipe: the hot isostatically pressed blank was loaded into a ceramic barrel preheated to 450°C, and the heating rate was controlled at 5°C / min; the pipe was extruded at a speed of 20 mm / s through a screw extruder, and the hydraulic pressure was adjusted according to the pipe diameter (Φ2-5mm was set to 4-6MPa, Φ5-10mm was set to 8-12MPa); the cooling step adopted a combination of water cooling + air cooling, the cooling rate was controlled at 120 K / s, and the final cooling temperature was controlled at 100°C to avoid thermal stress cracking.
[0055] Comparative Example 1
[0056] The other conditions are the same as those in Example 1, except that: during friction stirring extrusion, the first stage is omitted, that is, the second stage is directly entered, at which the speed is directly 150 rpm, the temperature is raised to 450°C, and the hydraulic pressure is increased to 1.5 MPa; during the friction extrusion stage, the hydraulic pressure needs to be adjusted according to the thickness and diameter of the tube wall (3 MPa is set for a wall thickness of 3 mm), the grinding head speed is controlled at 150 rpm and the mold is preheated to 300°C, and the interface peeling is prevented by gradient speed control (i.e., the grinding head inlet speed is 150 rpm and the outlet speed is 135 rpm); finally, inert gas cooling (argon flow rate 50 L / min) combined with a water cooling jacket is used to achieve rapid cooling (rate ≥ 150 K / s), the final cooling temperature is controlled at 80°C to avoid residual stress, and the aluminum layer is protected from oxidation by a nitrogen curtain. The grains of the obtained product are coarsened to 100 μm.
Claims
1. A method for preparing a tube of an aluminum-copper gradient composite material, characterized in that: The steps include: Step 1 A blank is prepared according to the designed composition; in the blank, the copper content of at least two regions differs by more than 1wt%; Step 2 The obtained blank is added into a silo, and an aluminum-copper gradient composite material is prepared by a friction stirring extrusion process; When the aluminum-copper gradient composite material is prepared by the friction stir extrusion process, the initial rotation speed of the grinding head is set to 30-50 rpm / min, and the rotation speed is maintained after contacting the raw materials in the silo, so that the temperature of the grinding head gradually increases to A℃; during the preheating stage of the grinding head, the pressure applied by the hydraulic system is 0.3-0.8 MPa to ensure that the initial pressure when the grinding head contacts the raw materials is moderate to avoid premature deformation or extrusion of the material; the value of A is 180-220; when the preheating temperature of the grinding head reaches A℃, the staged heating begins. In the first stage, the speed of the grinding head is increased to 100-120 rpm / min, the temperature is raised to 350-400℃, and the hydraulic pressure is maintained at 0.5-1.0 MPa to maintain plastic fluidity; in the second stage, the speed is further increased to 150-180 rpm / min, the temperature is raised to 450-550℃, and the hydraulic pressure is gradually increased to 1.5-3.0 MPa during the implementation of the second stage to promote copper-aluminum interface diffusion and compensate for the low plasticity of aluminum; Step 3 When the temperature of the grinding head rises to 450-550°C, the hydraulic pressure is adjusted according to the wall thickness of the pipe and the grinding head speed is controlled at 150-200 rpm and the mold is preheated to 300-400°C. At the same time, the interface peeling is prevented by gradient speed control; the gradient speed is 150-200 rpm at the inlet end of the grinding head and the outlet end speed is reduced by 5%-15%, and the speed decreasing distribution is achieved by the axial displacement of the spiral rolling die; Adjusting the hydraulic pressure according to the pipe wall thickness means: when the pipe wall thickness is 1-3mm, the hydraulic pressure is set to 2~4 MPa; when the pipe wall thickness is greater than 3mm and less than or equal to 7mm, it is set to 4~6 MPa; Step 4 The pipe prepared by the friction stir extrusion process is cooled to 50-80°C at a cooling rate greater than 100K / s to obtain the product.
2. The method for preparing a tube of an aluminum-copper gradient composite material according to claim 1, characterized in that: The density of the blank in step 1 is ≥ 95% of the theoretical density.
3. The method for preparing a tube of an aluminum-copper gradient composite material according to claim 1, characterized in that: The blank may include at least three parts, which are a high copper area, a middle copper area, and a low copper area; the middle copper area is located between the high copper area and the low copper area, the copper content of the high copper area is greater than that of the middle copper area and the low copper area, and the copper content of the middle copper area is greater than that of the low copper area.
4. The method for preparing a tube of an aluminum-copper gradient composite material according to claim 3, characterized in that: The copper content in the low copper zone is greater than or equal to 50%; the copper content in the medium copper zone is greater than or equal to 70%.
5. The method for preparing a tube of an aluminum-copper gradient composite material according to claim 3, characterized in that: The high copper area, medium copper area, and low copper area are composed of copper and aluminum; or Made of copper and aluminum alloy.
6. The method for preparing a tube of an aluminum-copper gradient composite material according to claim 3, characterized in that: When preparing the blank, the raw materials used are A1060 aluminum alloy powder with a purity of ≥99.0% and a particle size of 20-50μm. Fine powder is used to improve the density of the blank; C1100 electrolytic copper powder with a purity of ≥99.5% and a spherical fine powder with a particle size of 20-50μm is used to improve the conductivity of the material, improve powder fluidity, and reduce powder segregation.
7. The method for preparing a tube of an aluminum-copper gradient composite material according to claim 3, characterized in that: In the high copper area, the aluminum content is less than or equal to 10%; In the medium copper zone, the aluminum content is less than or equal to 30%, but greater than the aluminum content in the high copper zone; In the low copper zone, the aluminum content is less than or equal to 50%, but greater than the aluminum content in the medium copper zone.
8. The method for preparing a tube of an aluminum-copper gradient composite material according to claim 3, characterized in that: When mixing the raw material powder in the high copper area, a three-dimensional motion powder mixer is used, and the speed is controlled at 200rpm / min and the time is 2 hours; When mixing the raw material powder in the middle copper area, a three-dimensional motion powder mixer is used, and the speed is controlled at 150rpm / min and the time is 4 hours; When mixing the raw material powder in the low copper area, a three-dimensional motion powder mixer is used, and the speed is controlled at 100 rpm / min and the time is 6 hours.
9. The method for preparing a tube of an aluminum-copper gradient composite material according to claim 3, characterized in that: Laying evenly mixed high copper region raw material powder according to a set thickness, and then laying evenly mixed high copper region raw material powder according to a set thickness; obtaining a high copper region raw material powder layer, and then laying a medium copper region raw material powder layer on the high copper region raw material powder layer, and laying a low copper region raw material powder layer on the medium copper region raw material powder layer; and then pressing to obtain a preform, wherein the density of the preform is ≥95% of the theoretical density; or The high and low copper area raw material powders are evenly mixed and laid according to a set thickness, and then the low copper area raw material powder is evenly mixed and laid according to a set thickness; a low copper area raw material powder layer is obtained, and then a medium copper area raw material powder layer is laid on the low copper area raw material powder layer, and a high copper area raw material powder layer is laid on the medium copper area raw material powder layer; and then pressed to obtain a blank, wherein the density of the blank is ≥95% of the theoretical density.
10. The method for preparing a tube of an aluminum-copper gradient composite material according to claim 3, characterized in that: During the pressing process, the pressure was controlled at 200 MPa and the holding time was 2 hours.
Citation Information
Patent Citations
A method for providing plastic zone extrusion and a method for providing friction stir
CN102371286A
Copper-aluminum alloy layered composite material with gradient fault energy interface and preparation method of copper-aluminum alloy layered composite material
CN116511483A
Extrusion molding method for al base rapidly cooling solidified powder
JP1990088704A
Devices and Methods for Performing Shear-Assisted Extrusion and Extrusion Processes
US20210402471A1